Factors deteriorating effectiveness of Broad-Based Black Economic Empowerment (B-BBEE) in South African: A Systematic Literature Review - Geqeza, Awonke (Journal of Ecohumanism, 2025)
One of South Africa's prominent policies aimed at addressing economic injustices that were created by apartheid is Broad-Based Black Economic Empowerment (B-BBEE). This polices encourages black ownership, participation, and skill development in business that wants to trade with the state. Even though the B-BBEE was meant to enhance the redistribution of economic wealth, evidence indicates that inequality, poverty, and unemployment on a large scale continues to rise. This systematic literature review integrates academic and policy discussions to uncover the fundamental factors that undermines the efficacy of B-BBEE. In this review, peer-reviewed papers, policy reports and book chapters published between 2003 and 2024 were examined. The emphasising was embedded on persistent challenges such as elite capture, fronting and compliance-driven practices, corruption and rent-seeking in public procurement, minimal effects on poverty alleviation, suboptimal skills development outcomes, policy ambiguity, and insufficient monitoring and enforcement mechanisms. The results suggest that B-BBEE has helped create a black middle class and encouraged some business growth, but it doesn't work as well as it could because of problems with its design and implementation. The review concludes that for B-BBEE to achieve genuine transformation, a shift towards inclusive, grassroots empowerment should be considered.